PENGARUH KOMPENSASI, PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DENGAN LOYALITAS KARYAWAN SEBAGAI VARIABEL INTERVENING - Mahendra, Novian Wahyu; Sutrisno, Sutrisno; Meiriyanti, Rita (Transpublika Publisher, 2023)
This research aims to determine the effect of providing compensation, job training, and work motivation on employee performance with employee loyalty as an intervening variable at UMKM HM Putra Emping. Based on this, this research is entitled